Динамика факторов протестных практик населения Украины - Резник, А. (Iнститут соціології НАН України, 2009)
The article tracks the dynamics of protest practices in Ukrainian society in a period after so called "Orange revolution". The author selects the structural, socio-psychological and resource mobilization approaches to explanation of the protest behaviour factors. Upon this ground, these factors are aggregated in two explanatory models. Structural factors form the model of social disruption. At the same time the resource mobilization and socio-psychological factors in a ensemble form the model of civil voluntarism. The author advances two hypotheses about the factors of the protest practices determination. In order to clarify these hypotheses he applies the method of binary logistic regression. An analysis has prove that civil activity caused by events of "Orange revolution" was conditioned by regional and geopolitical dissidences, but later on the protest practices were determined mainly by resource and sociopsychological stimuli. The results of analysis reveal that the value and world view stratification of society has not influenced the protest behaviour. This developments can explain to some extent the absence of serious social conflicts in Ukraine.